Cholesteryl Ester Storage Disease: an Easily Missed Diagnosis in Oligosymptomatic Children - Freudenberg, F.; Bufler, P.; Ensenauer, R.; Lohse, P.; Koletzko, S. (Zeitschrift für Gastroenterologie, 2013)
Cholesteryl ester storage disease (CESD) is a rare, autosomal recessively inherited disorder resulting from deficient activity of lysosomal acid lipase (LAL). LAL is the key enzyme hydrolyzing cholesteryl esters and triglycerides stored in lysosomes after LDL receptor-mediated endocytosis. Mutations within the LIPA gene locus on chromosome 10q23.2-q23.3 may result either in the always fatal Wolman disease, where no LAL activity is found, or in the more benign disorder CESD with a reduced enzymatic activity, leading to massive accumulation of cholesteryl esters and triglycerides in many body tissues. CESD affects mostly the liver, the spectrum is ranging from isolated hepatomegaly to liver cirrhosis. Chronic diarrhea has been reported in some pediatric cases, while calcifications of the adrenal glands, the hallmark of Wolman disease, are rarely observed. Hypercholesterolemia and premature atherosclerosis are other typical disease manifestations. Hepatomegaly as a key finding has been reported in all 71 pediatric patients and in 134 of 135 adult cases in the literature. We present a 13-year-old boy with mildly elevated liver enzymes in the absence of hepatomegaly, finally diagnosed with CESD. Under pravastatine treatment, the patient has normal laboratory findings and is clinically unremarkable since 5 years of follow-up. To our knowledge, this is the first pediatric case of genetically and biopsy confirmed CESD without hepatomegaly, suggesting that this diagnosis can be easily missed. It further raises the question about the natural course and the therapy required for this oligosymptomatic form.
Keywords: liver; cholesteryl ester storage disease (CESD); lysosomal acid lipase; atherosclerosis; LDL cholesterol